Development of TikTok-Based E-Poster Learning Media for Green Chemistry Education in High Schools - Abdul Gani; Muhammad Nazar; Resfie Zalnisa Razma (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
The low level of students' interest in green chemistry presents a significant challenge for educators in creating engaging instructional media. An innovative approach to address this issue is the development of TikTok-based e-poster learning media. This study aims to evaluate the feasibility of TikTok-based e-poster media for green chemistry content and analyze the responses of both teachers and students to its implementation. Using a research and development (R&D) approach based on the ADDIE model, data were collected through interviews, needs analysis, assessments of the e-poster's feasibility and reliability, and evaluations of teachers' and students' responses. The study was conducted at a public high school, involving 26 students from Class X IPAS 1. The findings revealed that the e-poster achieved a validity score of 94.80%, classified as very feasible, and a reliability coefficient of 0.86, indicating very high reliability. Teachers' responses averaged 92.80%, and students' responses averaged 92.30%, both falling within the very good category. Therefore, the TikTok-based e-poster learning media is highly effective and can serve as a valuable model for future instructional media development.